PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI DAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI (Studi Empiris Seluruh Manajer Rumah Sakit Umum Pemerintah di Provinsi Riau) - Agustia, Dwi; Azlina, Nur; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to identify and analyze about (1) The effect of budgetary participation on managerial performance, (2) The effect of budgetary participation on managerial performance with organizational commitment as moderating variable, and (3) The effect of budgetary participation on managerial performance with locus of control as moderating variable. Study was conducted at government general hospital in Riau Province, which amount to 13 general hospital. The data used in this research was primary data with questionnaire as an instrument. The method that used to the sample selection was simple random sampling. The number of samples in this research were 120 respondents. Hypothesis test used in this research was statistical t-test. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 17.0 for Windows as data processing software program. Results of hypothesis test using statistical ttest showed the significant value of budgetary participation variable 0.000 < 0.05, which means that H1 accepted, the organizational commitment variable 0.033 < 0.05, which means that H2 accepted, and locus of control variables 0.021 < 0.05, which means the H3 accepted. The results showed budgetary participation, organizational commitment, and locus of control has effect on managerial performance.Keywords : budgetary participation, managerial performance, organizational commitment, and locus of control.